Nominal stability and Swiss monetary regimes over two centuries - Daniel Kaufmann (ETH Zurich, KOF Swiss Economic Institute, 2015)
This paper documents nominal stability in Switzerland from 1805 to 2013 using a data set on annual price, wage and nominal GDP changes. The trends of these indicators are estimated by an unobserved-components stochastic-volatility model in order to control for short-term fluctuations and measurement error. Based on a narrative analysis of these trends five main findings emerge. (i) Fiat currency regimes in Switzerland provided a relatively stable monetary background even compared to the metal-currency regimes before WW1. (ii) The flexible inflation targeting regime adopted in December 1999 has performed best over the last two centuries measured by today's definition of nominal stability. (iii) Fiat currency regimes without clearly communicated nominal price anchor (Bretton Woods System and monetary targeting) were characterised by an inflation bias. (iv) The metal-currency regimes (competing currencies and bimetallism before World War 1, and to some extent flexible inflation targeting, were associated with a deflation bias. (v) Persistent deflations in terms of the CPI only occurred under metallic regimes before WW2. These episodes were accompanied by falling nominal GDP, falling employment but relatively stable hourly wages.
Keywords: E31; C22; 330; Nominal stability; price stability; monetary regimes; monetary history; unobserved-components stochastic-volatility model